The Constitutional and Legal Status of the Deputy of the Representative Body of Local Self-Governmentin the Russian Federation and the Republic of Kazakhstan - Z. Z. Tasybaeva (Сибирское юридическое обозрение)
The author considers the elements of the constitutional legal status of the deputy of the representative body of local self-government. The article analyzes the scientific and research literature on this issue. The relevance of the proposed topic is determined by the lack of scientific studies investigating this problem since 2008. During this time, the legislation of the Republic of Kazakhstan and the Russian Federation has undergone significant changes. Using the comparative legal method, the author explores the elements of constitutional legal status (age, citizenship, education, term of office, responsibility, forms of activity, etc.) of deputies of representative local governments on the example of the deputy body of the Omsk City Council and Maslikhat of Astana. The ways of further improvement of the legal regulation of the constitutional and legal status of deputies of representative bodies of local self-government of the Republic of Kazakhstan are proposed.